Testing preferences for basic income - Ana Helena Palermo Kuss (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2019)
Inspired by Fröhlich and Oppenheimer (1990), an experimental survey in the lab was designed to find out if preferences for three different redistribution schemes differ under a veil of ignorance. The three schemes are a stylized version of the status quo German welfare state (A), a control scheme without income taxation and redistribution (B) and one in which a flat tax-financed basic income is paid to all (C). Furthermore, the study investigates whether the introduction of a basic income induces a decrease in the time allocation to paid and unpaid work. The results point to no significant difference in allocated working hours between A and C. Concerning preferences, access to information on implications of schemes and self-interest played a central role in their definition.
Keywords: C91; I38; J22; 330; lab experiment; basic income; welfare state; Germany; time allocation; constitutional economics; labor supply